No Influence of Nonivamide-nicoboxil on the Peak Power Output in Competitive Sportsmen - Schörkmaier, Theresa; Wahl, Yvonne; Brinkmann, Christian; Bloch, Wilhelm; Wahl, Patrick (International Journal of Sports Medicine, 2021)
Recent studies have shown that the oxygenated hemoglobin level can be enhanced during rest through the application of nonivamide-nicoboxil cream. However, the effect of nonivamide-nicoboxil cream on oxygenation and endurance performance under hypoxic conditions is unknown. Therefore, the purpose of this study was to investigate the effects of nonivamide-nicoboxil cream on local muscle oxygenation and endurance performance under normoxic and hypoxic conditions. In a cross-over design, 13 athletes (experienced cyclists or triathletes [age: 25.2±3.5 years; VO2max 62.1±7.3 mL·min−1·kg−1]) performed four incremental exercise tests on the cycle ergometer under normoxic or hypoxic conditions, either with nonivamide-nicoboxil or placebo cream. Muscle oxygenation was recorded with near-infrared spectroscopy. Capillary blood samples were taken after each step, and spirometric data were recorded continuously. The application of nonivamide-nicoboxil cream increased muscle oxygenation at rest and during different submaximal workloads as well as during physical exhaustion, irrespective of normoxic or hypoxic conditions. Overall, there were no significant effects of nonivamide-nicoboxil on peak power output, maximal oxygen uptake or lactate concentrations. Muscle oxygenation is significantly higher with the application of nonivamide-nicoboxil cream. However, its application does not increase endurance performance.
Keywords: muscle oxygenation; near-infrared spectroscopy (NIRS); cycling; hypoxia